Dual-Layer Natamycin and Boric-Acid-Reinforced PVA/Chitosan by 3D Printing and Electrospinning Method: Characterization and In Vitro Evaluation - Oktay, Busra; Ciftci, Fatih; Erarslan, Azime; Ozerol, Esma Ahlatcioglu (MDPI, 2025)
This study presents the development and comprehensive characterization of biopolymer-based nanofibrous composites composed of polyvinyl alcohol (PVA), chitosan (CS), boric acid (BA), and a natural antifungal agent natamycin (NAT), designed for therapeutic applications. A dual-layer 3D-fiber composite (PVA/CS/BA_PVA/NAT) was successfully fabricated using a layer-by-layer 3D bioprinting technique and electro-spinning, integrating BA into the core matrix and NAT into the outer layer. Mechanical tests revealed a significantly improved elastic modulus of 763.04 +/- 14.54 MPa and the highest ultimate tensile stress (50.45 +/- 2.58 MPa) among all samples. Despite a moderate strain at break (11.77 +/- 0.49%), the composite preserved sufficient elasticity suitable for biological interfaces. Morphological assessment via SEM confirmed the successful deposition of continuous and bead-free nanofibers, with controlled fiber alignment and reduced average fiber diameters, especially in the BA-incorporated structure. The dual-layered system displayed enhanced uniformity and structural coherence. The drug release analysis demonstrated sustained NAT delivery over a 90 min period. Kinetic modeling showed a high correlation with the Korsmeyer-Peppas model (R2 > 0.99), suggesting diffusion-controlled release, supported by the Korsmeyer-Peppas model's Fickian diffusion exponent. In contrast, zero- and first-order models exhibited weaker fits, underscoring the relevance of a matrix-based release mechanism governed by the layered configuration. Crucially, antifungal assays against Candida albicans revealed substantial bioactivity. The PVA/CS/BA_PVA/NAT formulation achieved the largest inhibition zone (1.64 +/- 0.13 cm), significantly outperforming single-layer controls such as PVA/CS/BA (1.25 +/- 0.08 cm) and PVA/CS_PVA/NAT (1.43 +/- 0.08 cm), while neat PVA exhibited no inhibition. These results confirm the synergistic antifungal efficacy of BA and NAT within the dual-layer structure. Together, these findings highlight the potential of the 3D-printed PVA/CS/BA_PVA/NAT composite as a mechanically robust, morphologically optimized, and bioactive platform for antifungal therapy and wound-healing applications.
Keywords: 3D printing; antifungal; boric acid; nanofibers; natamycin; wound dressing; HYDROXYAPATITE NANOPARTICLES; FABRICATION; SURFACTANT; MORPHOLOGY; SCAFFOLDS; CHITOSAN; RELEASE; SOLVENT; Polymer Science